Uji Pemberian Air Limbah Kolam Ikan Terhadap Pertumbuhan Bibit 3 (Tiga) Varietas Padi (Oryza sativa L.) - Indah Sufiani; Akhmad Gazali; Hairu Suparto (Universitas Lambung Mangkurat, 2022)
Rice (Oryza sativa L.) is a plant that produces rice as a staple food. One of the important stages in rice the nursery stage. Good rice seeds are determined from the nursery process. Fertilization at the nursery stage aims to stimulate plant growth. Fish pond waste water is organic fertilizer which contains high organic matter. This study aims to determine the effect of giving a combination of several volumes of fish pond wastewater on the growth of seeds of 3 (three) rice varieties and to find out the best treatment of giving a combination of several volumes of fish pond waste water on the growth of seeds of 3 (three) rice varieties. This research was conducted in the greenhouse of the Agroecotechnology Departement, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru from June to July 2020. The study used a completely randomized design (CRD) 1 single factor with 12 combinations of several volumes of fish pond wastewater with three rice varieties repeated 3 times in order to obtain 36 experimental units. The observation parameters were seed height, leaf color, root length, header length, root wet weight, wet weight of the header, and the percentage of growing seeds. The treatment had a significant effect on seed height, shoot length, root wet weight, shoot wet weight and seedling percentage growth, but did not affect leaf color and root length. The best treatment is found in L3V3, namely the provision of 1000 ml fish pond wastewater for inpara 2 varieties.